(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate skin test results in patients with suspected immediate hypersensitivity to Platinum agents and Taxanes. Methods: A cross-sectional, retro-prospective descriptive study was conducted on patients with suspected immediate hypersensitivity to Taxanes or Platinum agents. The subjects were examined at the Allergen Department – Center for Allergology and Clinical Immunology over a 2-year period, from September 2023 to September 2025. Results: The study included 102 patients who underwent 215 skin prick tests (SPT) and 108 intradermal tests (IDT). Only 16 patients yielded positive skin test results (10 SPTs and 6 IDTs) to either Platinum or Taxane agents. Among these, Oxaliplatin exhibited the highest rate of positive skin tests, while Docetaxel showed the lowest. No cross-reactivity between the agents was detected. Conclusion: Skin tests in patients with suspected hypersensitivity to Platinum agents and Taxanes were predominantly negative. This supports the hypothesis that the underlying mechanism of chemotherapy-induced allergy is primarily non-IgE-mediated.